Analysing the Pragmatics of Speech Acts in Sitcom and Drama Audiovisual Genres - Peñarroja, Manuel Rodríguez (Cambridge Scholars Publisher, 2020)
This book provides positive evidence regarding the validity of the language used in sitcom and drama audiovisual genres and its possible applicability to the teaching of pragmatics in English as second and foreign language contexts. The first part of the text includes a description of pragmatics and its components, speech act theories development, and the use of audiovisual input for the teaching of pragmatic aspects. The second section is devoted to the sitcom and drama transcripts analysis of direct and indirect realisations of multiple speech acts as pragmalinguistic resources, sociopragmat.